CHARACTERISTICS CYBER CRIME AND DYNAMICS OF THE IMPLEMENTATION LOCUS DELICTI THEORY BY LAW ENFORCEMENT OFFICIALS IN INDONESIA - Shidiq, Muhammad Permana (Universitas Serang Raya, 2024)
Abstract The implementation of the locus delicti theory in cybercrime faces various complexities. This is due to the special characteristics of cybercrime, where the use of computers as a tool of crime often results in the perpetrator, victim, and impact of the crime being in different locations. This condition has caused debate among law enforcement officials regarding the determination of the right location as the place where the crime occurred. The purpose of this research is to see the implementation of the locus delicti theory in cyber crime by law enforcement officials in Indonesia. The research method applies normative juridical, as well as the descriptive nature of analysis. This research approach uses a theoretical approach, legal principles, a legal rule approach, and a case approach collected through literature studies, data collection techniques, and interviews. After all the data is collected, it is then analyzed qualitatively to produce several conclusions. The locus delicti theory has a necessary position in law enforcement efforts. However, in practice, this theory is not always applied in every case of cyber crimes, but only becomes a reference when the provisions in Article 84 Paragraph (2) of the Criminal Code cannot be applied optimally. Therefore, regulatory reform and a more flexible approach are needed in the application of locus delicti theory in the future.